Regional innovation systems: what can we learn from 25 years of scientific achievements? - Fernandes, Cristina (2021)
The regional innovation systems (RIS) concept has become popular among academics, political decision-makers and regional stakeholders of innovation. Understanding the competitive dynamics of RIS and their impact on regional competitiveness today has thus become a priority. This paper provides researchers, academics, political decision-makers and other interested parties with a map of the different approaches to RIS, aiding in the definition of new territorial innovation policies. With a co-citation resource approach, an extensive search of the Web of Science database was carried out and it encountered four clusters in the literature on RIS: regional knowledge systems; regional institutional systems; regional research and development systems; and regional network systems. This correspondingly sets out new theoretical perspectives based on bibliometric analysis techniques and new paths for scientific reflection and research.